FROM DORMITORY WALLS TO MORAL WORLDS: EMPOWERING EDUCATORS AS MORAL ARCHITECTS IN INDONESIAN BOARDING-BASED MADRASAHS - Halimatussa'diyah Halimatussa'diyah; Ahmad Suriansyah; Ahmad Alim Bachri; Sulistiyana Sulistiyana (JURNAL EDUSCIENCE, 2026)
Purpose –This study explores the moral and pedagogical dimensions of teacher empowerment within the unique ecosystem of Indonesian boarding-based madrasahs. In these faith-oriented learning environments, educators are not only knowledge transmitters but also moral architects, shaping students' ethical consciousness and communal identity.Methodology – Employing a qualitative multiple case study design, data were collected through in-depth interviews, field observations, and document analysis across three boarding-based madrasahs in South Kalimantan.Findings – The findings reveal that teacher empowerment in these settings transcends administrative or instructional authority, evolving instead into a moral praxis grounded in Islamic values, reflective mentorship, and collective spiritual routines such as Qur’an recitation and muhasabah (self-reflection). Educators exercise moral agency through daily interactions in the dormitory, reinforcing discipline, empathy, and self-accountability. Leadership strategies—such as participatory mentoring, ethical modeling, and arts-based religious practices—serve as integral mechanisms for cultivating a holistic moral environment.Contribution – This study contributes to the growing discourse on teacher empowerment by highlighting how faith-driven moral leadership can be both contextually rooted and pedagogically transformative. It argues that moral empowerment is essential for sustaining ethical schooling cultures, particularly in residential educational settings where learning and living converge. The implications extend toward rethinking teacher development frameworks that integrate spirituality, reflective practice, and community-based moral agency.